Hope against hope a theological reflection on Psalm 22 - Prinsloo, G. T. M. (1995)
This paper focuses upon the problem of the relationship between the two 'parts' of Psalm 22, namely a lament (2-22) and a hymn of thanksgiving (23- 32). An exegete's views on this issue influence his/her thoughts on the theology of the psalm. The aim of the paper is to shed light upon the theological relevance of the psalm via a careful analysis of the psalm in its final form. This approach leads to the conclusion that the psalm consists of not two but four interrelated stanzas descriptionbing lament, prayer, praise and the universal kingship of Yahweh in one continuous, organic unit. The theology of the psalm can be summarised by the phrase 'hope against hope'. In spite of his seemingly hopeless situation, the psalmist still trusts in Yahweh. Hope never abandons him. Read in this way. Psalm 22 is a remarkably relevant prayer for believers today.
Keywords: Content; Cultic interpretation; Kingship ideology; Liturgy; Masoretic Text; Messianic-christological interpretation; Psalm 22; Redaction-historical interpretation; Relevant prayer today; Structure; Theological relevance of the psalm